Critical junctures in mobile capital - Pixley, Jocelyn, 1947-; Flam, Helena (Cambridge : Cambridge University Press, 2018)
During the recent financial crisis, the conflict between sovereign states and banks over who controls the creation of money was thrown into sharp relief. This collection investigates the relationship between states and banks, arguing that conflicts between the two over control of money produces critical junctures. Drawing on Max Weber's concept of 'mobile capital', the book examines the mobility of capital networks in contexts of funding warfare, global bubbles and dangerous instability disengaged from social-economic activity. It proposes that mobile capital is a primary feature of capitalism and nation states, and furthermore, argues that the perennial, hierarchical struggles between states and global banks is intrinsic to capitalism. Featuring authors writing from an impressively diverse range of academic backgrounds (including sociology, geography, economics and politics), Critical Junctures in Mobile Capital presents a variety of analyses using current or past examples from different countries, federations, and of differing forms of mobile capital.
aMachine generated contents note: Introduction Jocelyn Pixley; 1. Sovereign nations and the governance of international finance Renate Mayntz; 2. Coping with the dangerous component of capital flows and Asia's ineffective cooperation Iwan Azis; 3. How mobile capital plays off democracy - the Euro case and other federations Jocelyn Pixley; 4. Mobile capital as the ultimate form of war finance Luca Fantacci and Lucio Gobbi; 5. Capital moves financially - securitisation, value - and the emergent social relations of labour Dick Bryan and Michael Rafferty; 6. International money after the crisis. What do we know? Herman Mark Schwartz; 7. Beware of financialization! Emerging markets and mobile capital Andreas Nolke; 8. Lagoon immobility. The exceptional case of imperial Venice Sam Whimster; 9. 'Convenient reverse logic' in mobile capital's inequalities Jocelyn Pixley; 10. Imagine: grassroots against financialization Helena Flam; 11. Money, state and capital: the long-term perspective Helmut Kuzmics; 12. Super diversity, exploitation and migrant workers Shaun Wilson; 13. The bitcoin or the reality of a waking dream Massimo Amato; 14. Capital mobility and the fragmentation of monetary sovereignty David Woodruff; 15. Surrogate currencies: Sardex Laura Sartori; Index.
Title from publisher's bibliographic system (viewed on 26 Feb 2018).
Keywords: Capital movements